Subclinical Pregnancy Toxemia-Induced Gene Expression Changes in Ovine Placenta and Uterus - Kasimanickam, Ramanathan K. (Frontiers in Veterinary Science, 2016)
The objective was to elucidate gene expression differences in uterus, caruncle, and cotyledon of ewes with subclinical pregnancy toxemia (SCPT) and healthy ewes, and to identify associated biological functions and pathways involved in pregnancy toxemia. On Day 136 (±1 day) post-breeding, ewes (n = 18) had body condition score (BCS; 1–5; 1, emaciated; 5, obese) assessed, and blood samples were collected for plasma glucose and β-hydroxybutyrate (BHBA) analyses. The ewes were euthanized, and tissue samples were collected from the gravid uterus and placentomes. Based on BCS (2.0 ± 0.02), glucose (2.4 ± 0.33), and BHBA (0.97 ± 0.06) concentrations, ewes (n = 10) were grouped as healthy (n = 5) and subclinical SCPT (n = 5) ewes. The mRNA expressions were determined by quantitative PCR method, and prediction of miRNA partners and target genes for the predicted miRNA were identified using miRDB (http://mirdb.org/miRDB/). Top ranked target genes were used to identify associated biological functions and pathways in response to SPCT using PANTHER. The angiogenesis genes VEGF and PlGF, and AdipoQ, AdipoR2, PPARG, LEP, IGF1, IGF2, IL1b, and TNFα mRNA expressions were lower in abundances, whereas hypoxia genes eNOS, HIF1a, and HIF 2a, and sFlt1 and KDR mRNA expressions were greater in abundances in uterus and placenta of SCPT ewes compared to healthy ewes (P < 0.05). The predicted miRNA and associated target genes contributed to several biological processes, including apoptosis, biological adhesion, biological regulation, cellular component biogenesis, cellular process, developmental process, immune system process, localization, metabolic process, multicellular organismal process, reproduction, and response to stimulus. The target genes were involved in several pathways including angiogenesis, cytoskeletal regulation, hypoxia response via HIF activation, interleukin signaling, ubiquitin proteasome, and VEGF signaling pathway. In conclusion, genes associated with blood vessel remodeling were lower in abundances and that the genes associated with hypoxic conditions were greater in abundances in the uteroplacental compartment of SCPT ewes. It is obvious that the factors that influence placental vascular development and angiogenesis as noted in this study set the course for hemodynamic changes and hence have a major impact on the rate of transplacental nutrient exchange, fetal growth, and health of the dam.